THE USE OF PICTURES SERIES BASED ON LOCAL WISDOM IN TEACHING WRITING - Fitriana Hanifah; Ayu Istiana Sari (English Education Department Slamet Riyadi University Surakarta, 2023)
This research was find out whether the use of pictures series based on localwisdom can improve students' developing of ideas in writing narrative texts at one ofpublic junior high school in central java.This method used in this research was a Classroom Action Research. Theresearch was conducted in two cycles in April 2022/2023 academic year. The researchwas the 32 students at one of public junior high school in central java in 2022/2023academic year. In collecting the data, the researcher used test and non-test such asobservation, interview, and documentation. To analysis data, the researcher usedqualitative and quantitative data analysis. The qualitative data analysis method that wasused proposed by Miles and Huberman analysis that consisted of data collection, datareduction, data display, and conclusion. To analyze the quantitative data, the researcherused mean score of the test.The result of the research show that pictures series based on local wisdom canimprove the students’ developing of ideas in writing narrative texts. The improvementof the students’ writing skill can be seen from the students writing achievement. Theresult of mean score for pre-test was 55, in post-test 1, it was 64, and in post-test 2, itwas 75. It can be concluded that pictures series based on local wisdom can improve thestudents’ writing skill especially in developing idea the sequence of stories in writingnarrative text.Keywords: Writing Skill, Pictures Series Media, Classroom Action Research